Prophylactic Antibiotics After Stented, Distal Hypospadias Repair: Randomized Pilot Study - Stephen Canon MD; Mary K. Marquette MD; Adam Crane; Ashay Patel DO; Ismael Zamilpa MD; Shasha Bai PhD (SAGE Publishing, 2018)
The usage of prophylactic oral antibiotics following distal hypospadias repair with stenting has been recently challenged. This study evaluated the incidence of symptomatic urinary tract infections (UTIs) following stented, distal hypospadias repair and the impact of prophylactic antibiotic therapy. Subjects 0 to 5 years of age with distal hypospadias were randomized to either Group 1 (antibiotics) or Group 2 (no prophylactic therapy). Urinalysis/urine culture was obtained intraoperatively with no preoperative antibiotics given. Phone interviews at 1 month and 3 months after surgery were done. Forty-eight patients were successfully randomized to either Group 1 (24) or Group 2 (24). The incidence of symptomatic UTI in this pilot study is low, and prophylactic antibiotic therapy does not appear to lower the incidence of symptomatic UTI. A larger, randomized, multicenter trial is needed to determine whether antibiotic prophylaxis reduces the risk of symptomatic UTIs following stented, distal hypospadias repair.